Non-audit services and auditor independence: Norwegian evidence - Yu (Elli) Zhang; David Hay; Claus Holm (Cogent Business & Management, 2016)
We examine the effect on auditor independence of auditors providing non-audit services in the Norwegian audit market. We report the results of three tests of independence of mind and one test of independence in appearance. These tests find that there is a positive relationship between audit fees and non-audit fees, which does not suggest loss of independence. Further analysis using two-stage least squares shows that audit and non-audit fees are jointly determined, and the results are still not consistent with loss of independence. There is no relationship between the provision of non-audit services and the frequency with which auditors issue modified audit opinions. There is no association between non-audit services and audit tenure. Finally, we examine the relationship between unexpected or excess non-audit fees and cost of capital. There is no relationship. Our findings fail to find any evidence for loss of independence of mind or loss of independence of appearance as a result of providing non-audit services.
Keywords: 650